Efficiency Enhancement of Perovskite Solar Cells Based on Graphene Nanocomposites as Electrons and Holes Transport Layers - Hayder Hasan Ali (Iraqi Journal of Industrial Research)
This study investigates the use of TiO2/G and ZrO2/G transport layers in perovskite solar cells. The hydrothermal technique was used to synthesize the transport layers. According to the results, using TiO2/G as an electron transport layer enhances the transfer of negative charges from perovskites, which increases the efficiency of the solar cell. This is thanks to improved electrical conductivity and less loss of negative charges in the transport layer. The positive gap transition from the perovskite layer to the gap transport layer was enhanced using ZrO2/G. The chemical and physical properties of ZrO2/G help to build a strong interface with perovskite, which promotes gap crossing and reduces the loss of positive charges. Regarding the photonic layer, the efficiency of the solar cell increased significantly when CsPbBr3 quantum dots were used as the active element due to their strong abilities to absorb light from the visible light spectrum according to absorption spectrometry measurements. The efficiency of converting light into electrical charges increases because they can absorb more sunlight, including low-level solar energy. Quantum dots have efficient charge transfer paths, which reduces charge loss and improves conversion efficiency. CsPbBr3 quantum dots are chemically and crystallineally stable. These factors work together to increase the efficiency of the perovskite solar cell when using CsPbBr3 quantum dots from 10.004% to 10.425%.